Wave-porous structure interaction modelling using Improved Meshless Local Petrov Galerkin method. (September 2017) - Divya, R.; Sriram, V.
Highlights: Implementation of the porous flow models in a meshfree weak formulations. Numerical algorithms to treat the interface boundary in weak formulations. Comparison between different resistance terms used in porous models. Based on the developed model and the numerical analysis, it has been shown that the recurve profile attached to the top of the vertical wall was better. Abstract: This paper presents the application of the Improved Meshless Local Petrov Galerkin method with Rankine source (Sriram and Ma, 2012) Sriram and Ma (2012) for wave interaction with porous structure model. The mathematical model is based on a unified governing equation that incorporates both pure fluid and porous region. The porous flow model is based on the empirical resistance coefficients. The interface between the pure fluid and porous region is numerically treated using background nodes having the porosity information and interpolated over the particle using simplified finite difference interpolation method. The model is validated using the available experimental results for wave damping over the permeable bed. The developed model is used to analyse the different shape of the seawall such as flaring shaped seawall, recurve wall and vertical wall. Then the validated model is used for analysing the overtopping amount due to the effect of porous layer in-front of the different sea wall profile. Numerical expression for overtopping amount has been provided for the different configurations from the numerical model.